2016
DOI: 10.2463/mrms.2014-0125
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Hemangiomas: Factors Associated with Pseudo Washout Sign on Gd-EOB-DTPA-enhanced MR Imaging

Abstract: Purpose: Our study aim was to clarify the characteristics of hemangiomas with pseudo washout sign (PWS) by comparing their features with those of hemangiomas without PWS on gadolinium-ethoxybenzyl-diethylenetriaminepentaacetic acid (Gd-EOB-DTPA)-enhanced magnetic resonance (MR) imaging.Methods: We evaluated the features of hemangiomas on Gd-EOB-DTPA-enhanced MR imaging of 70 hepatic hemangiomas in 31 patients, investigating the presence of peripheral or central nodular enhancement, diffuse enhancement, and art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 34 publications
2
10
1
Order By: Relevance
“…The typical enhancement pattern for hemangioma is delayed phase enhancement on extracellular contrast agent based-enhanced imaging (32). However, previous studies report that a 'pseudo washoutʼ sign can be observed in hemangioma during the transitional phase using Gd-EOB-DTPA as the contrast agent, probably owing to the excellent liver to lesion contrast when compared to extracellular contrast agent (33,34). In the present study, 'pseudo washoutʼ sign is also observed in some cases.…”
Section: Discussioncontrasting
confidence: 54%
“…The typical enhancement pattern for hemangioma is delayed phase enhancement on extracellular contrast agent based-enhanced imaging (32). However, previous studies report that a 'pseudo washoutʼ sign can be observed in hemangioma during the transitional phase using Gd-EOB-DTPA as the contrast agent, probably owing to the excellent liver to lesion contrast when compared to extracellular contrast agent (33,34). In the present study, 'pseudo washoutʼ sign is also observed in some cases.…”
Section: Discussioncontrasting
confidence: 54%
“…an increased cost, 2) increased examination time with the addition of the hepatobiliary phase which may be 10 minutes to hours after contrast agent administration, 3) the characteristics of the late phase images are different compared to non-hepatobiliary specific agents [27] [28].…”
Section: Discussionmentioning
confidence: 99%
“…The differentiation of hemangiomas and metastasis is sometimes difficult [6] [28] [30]. When using Gd-EOB-DTPA as a contrast agent, the late phase is different compared to non-hepatobiliary specific contrast agents, because the contrast agent is taken in by hepatocytes, and may become a pitfall [28]. Although not statistically significant, an increase for the sensitivity of metastasis and hemangiomas was seen for both readers A and B with the addition of FLAIR.…”
Section: Discussionmentioning
confidence: 99%
“…Flash‐filling hemangioma may show APHE and pseudo‐washout in HSCM‐enhanced MRI 104,105 . In general, as hemangiomas show a bright T 2 signal, and no washout on MRI with ECCM, it may not be difficult to differentiate them from HCC.…”
Section: Liver Cancermentioning
confidence: 99%
“…Flash-filling hemangioma may show APHE and pseudo-washout in HSCM-enhanced MRI. 104,105 In general, as hemangiomas show a bright T 2 signal, and no washout on MRI with ECCM, it may not be difficult to differentiate them from HCC. However, on HSCMenhanced MRI, some hemangiomas may appear hypointense because of the contrast uptake of the background liver in TP, called "pseudo-washout".…”
Section: Intrahepatic Mass-forming Cholangiocarcinoma (Imcc)mentioning
confidence: 99%